Strategi Pengembangan Teknologi Pertanian Padi Sawah di Langkat Sumatera Utara - Rahmi Nofitasari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Langkat Regency is one of the five largest rice fields in North Sumatra. This is an excellent opportunity to become a rice barn in North Sumatra. So, agricultural technology is needed to support increasing rice productivity. The research aims to form a strategy for developing agricultural technology in Langkat. The development strategy produces SO (strengths-opportunities) strategies, WO (weaknesses-opportunities) strategies, ST (strengths-challenges) strategies, and WT (weaknesses-threats) strategies (North Sumatra. This research was conducted in 2023 with one respondent as a Langkat Regency Agriculture Service field instructor. This resource person was chosen because he was considered capable of describing internal and external problems in lowland rice farming in Langkat. This research used the SWOT tool to identify the IFAS and EFAS factors of lowland rice farming. The study results are accelerating agricultural technology to increase productivity, monitoring the performance of extension workers in reducing pest attacks, and increasing productivity, training, and providing insurance for farmers. The agricultural service collaborates with BMKG for information on extreme weather.